KUALIFIKASI FETISH SEBAGAI TINDAK PIDANA DALAM PASAL 335(AYAT1) KUHP(STUDI KASUS FETISH KAIN JARIK GILANG MAHASISWA: QUALIFICATION OF FETISH AS A CRIMINAL OFFICE IN ARTICLE 335(paragraph1) of the Criminal Code (CASE STUDY OF UNAIR STUDENT JARIK GILANG FETISH CASE - FIRMANSYAH, MOCH. AKBAR ALIF; S.H., M.H, EMMILIA RUSDIANA (NOVUM : JURNAL HUKUM, 2022)
Lately, there is a case with a large number of victims that is widely discussed by the public. This case is known as the Fetish Kain Jarik because the perpetrator has a sexual deviation in the form of sexual attraction to people wrapped in fabric. The perpetrator, who is a final semester student at a university in Surabaya, made many of his juniors to be his sexual objects. The interesting thing is, the perpetrator's actions cannot be categorized as sexual harassment because the perpetrator and the victim do not meet in person, but only through electronic media. This study aims to find out and also understand the qualifications of kain jarik Fetish as a criminal act in Article 335 paragraph (1) of the Criminal Code and appropriate criminal sanctions for kain jarik Fetish perpetrators. This research is a normative research using a statutory approach and a case approach. The statutory approach is carried out using the main legal source of the Criminal Code and the case approach is carried out using the fetish kain jarik case which is analyzed using a perscriptive technique.